Deuterated polyethylene nanowire arrays for high-energy density physics. (24th June 2021) - Capeluto, M. G.; Curtis, A.; Calvi, C.; Hollinger, R.; Shlyaptsev, V. N.; Rocca, J. J.
Abstract: The interaction of intense, ultrashort laser pulses with ordered nanostructure arrays offers a path to the efficient creation of ultra-high-energy density (UHED) matter and the generation of high-energy particles with compact lasers. Irradiation of deuterated nanowires arrays results in a near-solid density environment with extremely high temperatures and large electromagnetic fields in which deuterons are accelerated to multi-megaelectronvolt energies, resulting in deuterium–deuterium (D–D) fusion. Here we focus on the method of fabrication and the characteristics of ordered arrays of deuterated polyethylene nanowires. The irradiation of these array targets with femtosecond pulses of relativistic intensity and joule-level energy creates a micro-scale fusion environment that produced $2× {10}^6$ neutrons per joule, an increase of about 500 times with respect to flat solid CD2 targets irradiated with the same laser pulses. Irradiation with 8 J laser pulses was measured to generate up to 1.2 × 10 7 D–D fusion neutrons per shot.